Child marriage among boys in high-prevalence countries: an analysis of sexual and reproductive health outcomes - Christina Misunas; Colleen Murray Gastón; Claudia Cappa (BMC, 2019)
Abstract Background While the determinants and impacts of child marriage among girls have been well documented, little research exists on the practice among boys. This paper explores the sociodemographic profile of men who married by age 18 and assesses whether they are more or less advantaged than their peers in terms of their sexual and reproductive health outcomes. Methods This analysis used the most recent data from nationally representative household surveys for the 15 countries with the highest prevalence of marriage by age 18 among men aged 20-24 at the time of the survey. The prevalence of child marriage was then explored for the full cohort of men aged 20-49 through descriptive statistics and bivariate analysis. Available reproductive health indicators were explored, comparing men who married during childhood and men who married in adulthood. For the youngest and oldest cohorts, the total number of children fathered and the total ideal number of children were compared based on whether men married by age 18. Results For this subset of countries, the prevalence of child marriage among men aged 20-24 ranges from 8.4 to 27.9%. The practice appears most common among respondents living in the poorest households and in rural areas, and with no education or only primary schooling. Men who married as children appear less likely to have comprehensive knowledge of HIV than their peers who married in adulthood. Little difference among men who married by age 18 and those who married in adulthood was observed regarding knowledge or use of modern methods of contraception. In almost all countries with data, the odds of having fathered three or more children among men aged 20-29 are higher for those who married as children compared to their peers. In four countries, the odds of exceeding one's ideal family size among men aged 40-49 also appear higher among those who married during childhood compared to men who married at older ages. Conclusion These results highlight the need for further research to identify drivers of the practice and short- and long-term outcomes for men who married during childhood, specifically concerning fatherhood, fertility preferences, and completed family size.